2011
DOI: 10.1262/jrd.11-002s
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Neurokinin Receptors in the Control of Pulsatile Luteinizing Hormone Secretion in Rats

Abstract: Abstract. It has recently been shown that neurokinin B, a tachykinin, is associated with GnRH pulse generation in sheep and goats. The aim of the present study was to clarify the role of tachykinin receptors in the control of LH secretion in rats. To this end, we evaluated the effect of CS-003, an antagonist for all three neurokinin receptors (NK1, NK2 and NK3 receptors), on pulsatile LH secretion in both sexes of rats with different routes of administration. Both oral and third ventricular administration of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 59 publications
3
31
0
Order By: Relevance
“…Of note, this study showed that, in vitro, the activation of kisspeptin neurons by NKB was completely diminished only when all three neurokinin receptor (NKR) subtypeselective antagonists were concomitantly applied in the in vitro bath (de Croft et al 2013). This is in line with studies carried out in vivo indicating that blockade of all 3 tachykinin receptors (but not each one of them individually) prevented the compensatory rise of LH after gonadectomy (GDX) in rats (Noritake et al 2011). Therefore, considerable cross-reactivity exists between these receptor/ligand systems, and each one of these neuropeptides is capable of eliciting responses from all three neurokinin receptors (Cascieri et al 1992, Gether et al 1993, Beaujouan et al 2000.…”
Section: Introductionsupporting
confidence: 86%
See 2 more Smart Citations
“…Of note, this study showed that, in vitro, the activation of kisspeptin neurons by NKB was completely diminished only when all three neurokinin receptor (NKR) subtypeselective antagonists were concomitantly applied in the in vitro bath (de Croft et al 2013). This is in line with studies carried out in vivo indicating that blockade of all 3 tachykinin receptors (but not each one of them individually) prevented the compensatory rise of LH after gonadectomy (GDX) in rats (Noritake et al 2011). Therefore, considerable cross-reactivity exists between these receptor/ligand systems, and each one of these neuropeptides is capable of eliciting responses from all three neurokinin receptors (Cascieri et al 1992, Gether et al 1993, Beaujouan et al 2000.…”
Section: Introductionsupporting
confidence: 86%
“…Furthermore, KNDy cells are interconnected with NKB fibers within the ARC forming a tightly regulated network (Rance & Bruce 1994, Krajewski et al 2010. Indeed, a growing number of studies in multiple species from our lab and others support the ability of NKB, or the NKB receptor (NK3R) agonist senktide, to increase LH pulses (Grachev et al 2012, Navarro 2013, Goodman et al 2014 (Arisawa et al 1990, Kalra et al 1992, Sahu & Kalra 1992, Noritake et al 2011, de Croft et al 2013 including men (Coiro et al 1992). It is therefore plausible to speculate that these tachykinins are involved in the central regulation of GnRH release and may be additional elements to the GnRH pulse generator.…”
Section: The Current Model For the Gnrh Pulse Generatormentioning
confidence: 99%
See 1 more Smart Citation
“…This result has interesting parallels with a recent in vivo study in rats where a combined tachykinin receptor antagonist suppressed LH secretion, whereas individual tachykinin receptor antagonists were ineffective (57). In relation to in vivo studies, it is notable that many investigators have used Senktide to evaluate the effects of the NKB system on gonadotropin control.…”
Section: Nkb Acts Through Multiple Tachykinin Receptors To Activate Ksupporting
confidence: 60%
“…NKB preferentially binds and activates the neurokin 3 receptor (NK3R), although promiscuous binding to other neurokinin receptor subtypes has been implicated in the modulatory actions of NKB signalling in rodents [40,46]. The initial report of suppressed LH secretion following selective activation of NK3R in OVX + E 2 rats [47] prompted similar experiments in other species.…”
Section: Mechanisms Of Kndy Signallingmentioning
confidence: 99%